INFORMASI AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA MANAJER - Sriwidodo, Untung - (Universitas Slamet Riyadi, 2010)
ABSTRACT Each responsibility center have manager in charge of a activity that happened in center which responsibility head, and periodical the manager will justify result of its job to company head. Type of center responsibility there is four types that are earnings center, cost center, profit center and investment center. Responsibility accounting information useful in operation of management, because emphasizing at relation. Among information with manager in charge of to execution and planning. In evaluating measurement of manager performance center responsibility of answer there three used performance that is efficiency, effectiveness and economic. Keywords: center responsibility, control of management, manager performance.